Effects of Valsartan vs Amlodipin on renal function in salt loaded spontaneously hypertensive rats - Kalina Gjorgjievska; Dimce Zafirov; Maja Jurhar Pavlova; Svetlana Cekovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2014)
The goal of this study was to compare the effects of valsartan and amlodipin on the systolic blood pressure and parameters specific to the renal function in salt loaded spontaneously hypertensive rats (SHR). 32 male SHR were used at age of 20 weeks and body weight ranging between 265-300 g. From 8 weeks of age tab water was replaced with a solution of NaCl (1%) given ad libitum. Rats were divided into 2 groups: valsartan treated group SHRVAL (n=16) in which valsartan was given at a dose of 10 mg/kg b. w. and amlodipine treated group SHRAMLO (n=16) in which amlodipine was given at a dose of 5 mg/kg b. w. For a period of 12 weeks we have evaluated the effect of the investigated drugs on systolic blood pressure, body weight and renal function tests. In salt loaded rats amlodipine was more effective in reducing the systolic blood pressure in contrast to valsartan who had more pronounced effect on renal parameters most evident in proteinuria. Since both treatment groups have different mechanism of action a combination therapy may be beneficial in improving renal function in SHR rats.